Pengaruh Halal Knowledge dan Halal Awareness Daging Sapi Segar Tanpa Kemasan Terhadap Keputusan Pembelian - Anie Eka Kusumastuti; geovani gita jauhari (Jurnal Ilmiah Ekonomi Islam, 2025)
The halal certification process for fresh beef faces challenges due to many non-certified slaughterhouses, as seen in Bondowoso Regency, which has a large cattle population but lacks halal certification. The objective of this study was to ascertain the impact of halal knowledge and awareness on purchasing decisions for fresh, unpackaged beef in the Bondowoso Regency area. Total 98 respondents were selected using the purposive sampling method. The collected data is statistically analysed through a descriptive analysis, research instrument testing, classical assumption testing, and multiple regression analysis. The findings revealed that the majority of respondents were civil servants, with an average education level of a bachelor's degree, and the majority fell within the 21-36 age range. The results of the F-test indicated that the calculated F-value (35.543) was greater than the tabulated F-value (3.09), thereby rejecting the null hypothesis. Similarly, the results of the t-test indicates that both variables exert a considerable positive influence on purchasing decisions for fresh, unpackaged beef products, with a total impact of 41.6%. The findings of the research indicate that halal knowledge and halal awareness have a significant impact on the purchasing decisions of consumers for unpackaged fresh beef products.